2002
DOI: 10.1007/s00234-002-0780-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient and occupational dose in neurointerventional procedures

Abstract: Neurointerventional procedures can involve very high doses of radiation to the patient. Our purpose was to quantify the exposure of patients and workers during such procedures, and to use the data for optimisation. We monitored the coiling of 27 aneurysms, and embolisation of four arteriovenous malformations. We measured entrance doses at the skull of the patient using thermoluminescent dosemeters. An observer logged the dose-area product (DAP), fluoroscopy time and characteristics of the digital angiographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 12 publications
1
28
0
1
Order By: Relevance
“…However only 44% or 123 Gy cm 2 of the kermaarea product is due to the coiling procedure, 113 Gy cm 2 is due to treatment of vasospasm including a DSA and 47 Gy cm 2 is due to the DynaCT procedure. Hence the P KA from the coiling procedure alone is in fact identical to the results from our previous study, but lower than reported by Kemerink et al [22] (228 Gy cm 2 ). However, in this study (in contrast to Sandborg et al [15]), the estimated maximum skin doses are higher (Table 6) since we also include skin doses due to CT examinations during the patients' stay at the NSICU.…”
Section: Comparison With the Literaturesupporting
confidence: 90%
“…However only 44% or 123 Gy cm 2 of the kermaarea product is due to the coiling procedure, 113 Gy cm 2 is due to treatment of vasospasm including a DSA and 47 Gy cm 2 is due to the DynaCT procedure. Hence the P KA from the coiling procedure alone is in fact identical to the results from our previous study, but lower than reported by Kemerink et al [22] (228 Gy cm 2 ). However, in this study (in contrast to Sandborg et al [15]), the estimated maximum skin doses are higher (Table 6) since we also include skin doses due to CT examinations during the patients' stay at the NSICU.…”
Section: Comparison With the Literaturesupporting
confidence: 90%
“…Two investigations reported average procedural skin doses of 1-1.5 Gy. 4,5 Reduction of radiation dose from each individual diagnostic and interventional exposure is critical for minimizing total patient and, thereby, population dose. While many publications suggest strategies to this end, 4,6,7 few address the issue of cumulative dose during the hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern with Onyx is that the prolonged time of injection can expose patients to a higher dose of radiation; however, in one study, it was in the lower part of the range in which nonstochastic effects may arise (22). We did not observe hair loss in any of our patients.…”
Section: Discussionmentioning
confidence: 53%